E-procurement System and Public Contract Management Performance at Rwanda Biomedical Center - Uwimpeta, Ernestine; Akims, Malgit (Journal of Public Policy and Administration, 2025)
Purpose: To investigate the influence of the e-procurement system on public contract management performance at the Rwanda Biomedical Center (RBC). Methodology: A descriptive research design and a mixed-methods approach were utilized. Data were collected through interview guides, questionnaires, and secondary sources. Employing the purposive sampling method, the study had a sample size of 80 respondents selected from the target population of 102 individuals involved in the contract management process at RBC, using the Krejcie and Morgan (1970) Table. Findings: In line with regression analysis, findings revealed that among them, E-informing emerged as a highly effective component, with a β = 0.428 significantly enhancing contract management by facilitating timely communication, improving stakeholder coordination, and reducing information asymmetry. E-sourcing also showed a strong positive influence [β = 0.401] by promoting transparency and fairness in supplier selection, which directly contributed to better compliance and accountability in contract execution. E-contracting exhibited a moderate impact [β = 0.162], and e-payment demonstrated a minimal and statistically insignificant influence on overall contract management performance, despite contributing to financial accuracy and compliance. Unique Contribution to Theory, Practice and Policy: The study recommends that Rwanda Biomedical Center should prioritize enhancing e-informing systems by investing in capacity-building programs to improve stakeholder ICT proficiency and addressing technical challenges such as system downtimes. For e-payment, efforts should enhance its interoperability with other e-procurement tools such as e-purchasing, e-invoicing, automated payment processing, and cash flow management, and implementation barriers to maximize its transactional efficiency and accountability in financial processes.